2015
DOI: 10.24297/jaa.v4i2.4269
|View full text |Cite
|
Sign up to set email alerts
|

Biological indicators of soil quality in natural and cultivated subtropical systems

Abstract: The objective of this work was to evaluate the effects of forest conversion at to agricultural production on some biological indicators to quantify their relationship in subtropical ecosystems. The experimental design was in romized complete blocks, with four treatments: subtropical rainforest (F), yerba mate crops (I) (Ilex paraguariensis SH.); citrus crops (C) (Citrus unshiu Marc.); tobacco crops (T) (Nicotiana tabacum L.). Soil samples were taken from 0-0.10, 0.10-0.20, 0.20-0.30m deep. The variables measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On the one hand, sticky red soil could adsorb certain ferrous ions, which decreased the content of water‐soluble Fe 2+ in soil; on the other hand, the motion of ferrous ions in soil around rhizosphere was hindered owing to the water and gas permeability of red soil was poor (Silver et al, 2000; Toledo et al, 2013). Additionally, the results showed that in the two types of soils, the increase amplitude of browning scale of tobacco leaves of K326 variety was far larger than that of Hongda variety with increasing applied concentration of ferrous ions.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, sticky red soil could adsorb certain ferrous ions, which decreased the content of water‐soluble Fe 2+ in soil; on the other hand, the motion of ferrous ions in soil around rhizosphere was hindered owing to the water and gas permeability of red soil was poor (Silver et al, 2000; Toledo et al, 2013). Additionally, the results showed that in the two types of soils, the increase amplitude of browning scale of tobacco leaves of K326 variety was far larger than that of Hongda variety with increasing applied concentration of ferrous ions.…”
Section: Discussionmentioning
confidence: 99%
“…Particulate organic matter Both are positioned within the most sensitive indicators, helping to identify changes manifested at different depths and in the face of management practices. Organic phosphorus allows the prediction of nutrient availability in the short term (Toledo, Arzuaga et al 2018).…”
Section: Acceptmentioning
confidence: 99%
“…It represents the quantity of organic soil nitrogen that microbial activity can convert into soluble inorganic forms. Due to its sensitivity, it can be employed as an indicator of the production capacity and the nitrogen contribution of the soil, informing recommendations for nitrogen application (Toledo, Arzuaga et al, 2018). It emerges as a highly sensitive indicator of land-use changes in subtropical soils (Nuñez, Orwin et al, 2022).…”
Section: Acceptmentioning
confidence: 99%
See 2 more Smart Citations